E-learning course design in ADDIE methodology as a process in BPMN 2.0 - Bąkała, Anna; Bąkała, Marcin (Projektowanie kursu e-learningowego w metodyce ADDIE jako proces w notacji BPMN 2.0, 2020)
The aim of the article is to apply selected business processes modelling notation BPMN in e-learning design to enable the e-learning team to use ADDIE methodology decomposed as a process. In the first part of the article some basic issues of the educational and organizational context of the process are presented. The second part explains the ADDIE methodology. Next, BPMN implementation in designing the online course process is proposed. The article is an introductory part of research aiming to optimize e-learning creation processes in business
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 4 (58), s. 21-32
Keywords: informatyka ekonomiczna